ASSESSMENT OF GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE FOR QUANTITATIVE TRAITS IN CHILLI (CAPSICUM ANNUUM L.) - M. JANAKI,; L.NARAM NAIDU,; C. VENKATA RAMANA,; M. PARATPARA RAO, (The Bioscan, 2015)
The present investigation was carried out during kharif 2012-13 at Horticultural Research Station, Lam, Guntur with 63 genotypes of chilli (Capsicum annuum L.) in a randomized block design with two replications to estimate the genetic variability, heritability and genetic advance for ten quantitative traits. Analysis of variance revealed significant differences among the genotypes for all the traits studied indicating the presence of sufficient variability in the studied material. The PCV was higher than GCV and the difference between PCV and GCV was narrow for most of the characters revealing little influence of the environment in the expression of these traits. High magnitude of PCV and GCV were observed for per cent fruit set, number of fruits per plant, fruit diameter, average dry fruit weight, number of seeds per fruit and yield per plant suggesting the existence of wide range of genetic variability in the germplasm for these traits and thus the scope for improvement of these characters through simple selection would be better. High heritability coupled with high genetic advance as per cent of mean was observed for all the characters except days to 50 % flowering indicating the predominance of additive gene action making the simple selection more effective.